Angiotensin Converting Enzyme (ACE) Inhibitory Activity, Toxicity Test, and Phytochemical Analysis of Roselle Flower Extract - Yani, Ahmad; Venny Patricia (Window of Health : Jurnal Kesehatan, 2024)
Hypertension is still one of the biggest health problems in the world, including in Indonesia. The high prevalence rate has encouraged a lot of research to find antihypertensive drugs and other alternative healing methods, especially those using natural ingredients. One plant that has antihypertensive activity is the roselle flower (Hibiscus sabdariffa L.). This research aimed to observe the inhibitory activity of roselle flower extract on the angiotensin-converting enzyme (ACE), determine the potential toxicity of roselle flower extract on shrimp larvae (Artemia salina Leach), and determine the phytochemical content in it. Roselle flower simplicia was extracted using the maceration method using a 70% ethanol solvent. The extract obtained was then tested for its inhibitory activity against ACE photometrically using a microplate reader. The observed inhibitory activity was calculated in terms of IC50. The toxicity of the extract was determined by the brine shrimp lethality test (BSLT) to see how toxic the roselle flower extract was to shrimp larvae. The secondary metabolite content in the extract was determined qualitatively and quantitatively. The research results showed that the extraction yield obtained was 32,63%. The IC50 value of roselle flower extract against ACE was 295,36 ppm. The toxicity test on shrimp larvae showed that the LC50 value obtained was 334,02 ppm. The results of qualitative phytochemical tests show that roselle flower extract contained flavonoids, quinones, and steroids. The flavonoids and phenolic content in roselle flower extract were 0,42% and 0,91%, respectively. Based on these results, the phytochemical content of roselle flower extract inhibited ACE activity, and its compounds can be used as ingredients for developing hypertension drugs